Stand-up preaching - W. Wessels (Acta Theologica, 2023)
Stand-Up Preaching, as per the subject line, promises homiletic insights from contemporary comedians. I must admit that Myers engages with contemporary comedians and the theory of comedy, as far as I can discern, in the most thorough manner possible in a single book. The list of comedians he contemplates is exceptionally comprehensive, and it seems that every well-known comedian who has set foot on American soil has at least been mentioned. I found myself, throughout the book, researching the comedians he introduced for further context on these personalities and backgrounds. In that respect, this is a brilliantly researched work by Myers.